ON THE ROLE OF MUHAZRAM NARRATORS IN THE DEVELOPMENT OF HADITH SCIENCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This study explores the under-researched category of mukhāḍramūn (transitional narrators) and their significance in the development of hadith sciences. These individuals lived during both the pre-Islamic period (Jāhiliyya) and the early Islamic era, accepting Islam either during the Prophet Muhammad’s صلى الله عليه وسلم lifetime or shortly after his death, but did not meet him while in a state of belief.The research traces the terminological evolution and definitional nuances of mukhāḍramūn from both linguistic and hadith sciences perspectives, analyzing the differing views of prominent scholars such as al-Ḥākim al-Naysābūrī, Ibn al-Ṣalāḥ, al-ʿIrāqī, al-Suyūṭī, al-Sakhāwī, and ʿAlī al-Qārī. The paper highlights how hadith scholars classified mukhāḍramūn as a distinct generation located between the ṣaḥābah (companions) and tābiʿūn (successors), which holds critical implications for isnād (chain of transmission) analysis. The presence of these narrators in foundational works such as Ṣaḥīḥ Muslim and Musnad Aḥmad ibn Ḥanbal underscores their relevance, while biographical compilations by al-Dhahabī and Ibn Ḥajar al-ʿAsqalānī demonstrate scholarly efforts to catalog their narrations. The research further notes the disagreements over their exact status, whether they are a subcategory of the tābiʿūn or a distinct class altogether. By documenting their lives, contributions, and classifications, the article establishes the mukhāḍramūn as essential transmitters in hadith historiography and argues for deeper investigation into their role. Ultimately, this inquiry emphasizes the meticulous methods of early Muslim scholars in preserving the authenticity of hadith literature, and it proposes that further research on the mukhāḍramūn can enhance our understanding of transmission accuracy and the evolution of Islamic scholarly traditions.